Enhancing Reading Comprehension Through Systematic Vocabulary Instruction - Mahmud, Lida; Tryana, Tryana (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
This study examined whether Systematic Vocabulary Instruction (SVI) could improve first-semester university students’ reading comprehension through three instructional cycles. Systemic vocabulary development emphasizes understanding vocabulary not as isolated words, but as a network of interconnected meanings, integrated within language structures and communicative contexts. The primary objective of this study is to evaluate how systematic vocabulary instruction can improve reading comprehension skills, with a focus on first-semester university students who frequently struggle with academic texts. Using a qualitative descriptive research design through Classroom Action Research (CAR), this study has been conducted in three cycles involving planning, implementation, observation, and reflection. Data were collected through classroom observations, student reflections, pre- and post-intervention assessments, and open-question, ensuring a comprehensive analysis of pedagogical changes and student progress. This research found that Reading Comprehension can be achieved through Systematic vocabulary development by strengthening and enriching the language education literature on systems-based instruction, it leads to fostering students' independence and creativity in language exploration, equipping them to navigate complex texts more effectively. However, when this method applied into unfamiliar themes with developed complex material, it led students to an abstract domain that requires intensive scaffolding